2010
DOI: 10.1111/j.1600-0714.2010.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative immunohistochemical evaluation of CD68 and TRAP protein expression in central and peripheral giant cell granulomas of the jaws

Abstract: Immunohistochemical evidence of this study shows that giant cells and a group of mononuclear cells of stroma in both peripheral and central giant cell granuloma express TRAP antibody severely that is specific for osteoclast. Also, these cells are positive reactive to CD68, which is the macrophage marker and therefore it can be mentioned that giant cells are osteoclast, although their origins are macrophagic/monocytic or their precursors, and maybe mononuclear cells in stroma have a role in formation of giant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
4
26
0
1
Order By: Relevance
“…number of multinucleated giant cells containing 4 to 20 nuclei (aggregated or not) dispersed in the fibrous stroma in a perivascular or adjacent position to areas of hemorrhage (Figures 3 and 4). Round macrophages, deposition of hemosiderin, extravasated erythrocytes, foci of osteoid material (bone trabeculae), dystrophic calcification and predominantly mononuclear inflammatory infiltrate, particularly surrounding the periphery of the lesion, are also found (2,6,8,14,19,22,25,28,36,37) . Although multinucleated giant cells are present in large quantity, they are not regarded as proliferative cells.…”
Section: Central Giant Cell Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…number of multinucleated giant cells containing 4 to 20 nuclei (aggregated or not) dispersed in the fibrous stroma in a perivascular or adjacent position to areas of hemorrhage (Figures 3 and 4). Round macrophages, deposition of hemosiderin, extravasated erythrocytes, foci of osteoid material (bone trabeculae), dystrophic calcification and predominantly mononuclear inflammatory infiltrate, particularly surrounding the periphery of the lesion, are also found (2,6,8,14,19,22,25,28,36,37) . Although multinucleated giant cells are present in large quantity, they are not regarded as proliferative cells.…”
Section: Central Giant Cell Lesionsmentioning
confidence: 99%
“…Moreover, displacement of teeth, root resorption and perforation of the cortical bone may be observed (2,6,22,24,25,36,37) .…”
Section: Central Giant Cell Lesionsmentioning
confidence: 99%
“…Histopathological and immunohistochemical parameters have been evaluated in some studies to determine reliable markers related to their different biologic behavior. [35] Moreover, results have revealed that the use of quantitative methods helps to find hidden aspects of diseases that may be ignored in routine histolopathological assessments. However, because of the limited number of studies evaluating differences between these lesions, coming to a firm conclusion is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Central giant cell granuloma (CGCG) is less common than the peripheral variant and grows centrally in the jaws. [23]…”
Section: Introductionmentioning
confidence: 99%
“…The MGCs are positive for CD68 because of their macrophage/monocyte origin . These MGCs cells are also positive for tartrate‐resistant acid phosphatase receptors (TRAP) , calcitonin , receptor RANK; GRα, and CTR, and TRAP, VNR, calcitonin .…”
Section: Introductionmentioning
confidence: 99%